2021
DOI: 10.1002/jso.26762
|View full text |Cite
|
Sign up to set email alerts
|

Falciform ligament tubular graft for mesenteric‐portal vein reconstruction during pancreaticoduodenectomy 

Abstract: Background Portal vein resection and reconstruction in locally advanced pancreatic cancer represents a potentially curative treatment in selected patients without increasing surgical mortality. However, vascular reconstruction after segmental venous resection is challenging. The parietal peritoneum has emerged as a venous substitute but few reports include its use as a tubular graft. We report a retrospective series of portal vein reconstruction using a falciform ligament tubular graft during pancreaticoduoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Very recent results, reported by the study group of Balzan et al, showed in a small cohort of 8 patients promising results after application of falciform ligament tubular graft for the reconstruction of PV/VMS during Whipple procedure with vascular resection [ 22 ]. Seven of the 8 patients showed non-altered vascular patency in CT 6 months postoperatively and a partial thrombosis, clinically inapparent, was diagnosed in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent results, reported by the study group of Balzan et al, showed in a small cohort of 8 patients promising results after application of falciform ligament tubular graft for the reconstruction of PV/VMS during Whipple procedure with vascular resection [ 22 ]. Seven of the 8 patients showed non-altered vascular patency in CT 6 months postoperatively and a partial thrombosis, clinically inapparent, was diagnosed in one patient.…”
Section: Discussionmentioning
confidence: 99%